Strategizing Sister City Partnerships: Paradiplomacy, Bilateral Relations, and Sustainable Cooperation in Indonesia - Nadya, Annisa; Mahendra, Zulfan Fakhri; Yahya, Muhammad Muhajir (Universitas Muhammadiyah Yogyakarta, 2023)
This research explored the intricate dynamics of sister city cooperation within the framework of paradiplomacy and bilateral relations, with a specific focus on Indonesia's evolving landscape. By employing a qualitative methodology, the study provided a comprehensive understanding of the structured stages involved in establishing sister city partnerships, from meticulous planning and strategic alignment to the drafting and signing of the Memorandum of Understanding (MoU). It highlighted the critical role of governmental oversight, legislative approval, and the convergence of local autonomy with national strategies in shaping effective and sustainable international collaborations. Furthermore, the research identified significant challenges in implementation and sustainability, emphasizing the need for robust strategies and active community engagement. Through the lens of Indonesian sister city networks, the study revealed the multifaceted nature of these partnerships, incorporating economic, cultural, educational, and political dimensions. The research aims to offer valuable insights and strategies for policymakers, local government officials, and international organizations engaged in or considering sister city initiatives, contributing to a more nuanced understanding of how these partnerships can foster mutual growth and welfare enhancement.